2001
DOI: 10.1034/j.1600-0447.2001.103002122.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of poor 1‐year outcome of DSM‐III‐R major depression in the general population: results of the Netherlands Mental Health Survey and Incidence Study (NEMESIS)

Abstract: Poor outcome of major depression is frequent in the general population. Largely the same risk factors are involved as in clinical populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
158
3
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(171 citation statements)
references
References 35 publications
9
158
3
1
Order By: Relevance
“…In line with this hypothesis, studies have found that anhedonia can precede the onset of depression (Dryman and Eaton, 1991); shows temporal stability (Oquendo et al, 2004); predicts poor outcome 12 months later (Spijker et al, 2001); and is associated with dysfunctions within the brain reward system (Keedwell et al, 2005;Tremblay et al, 2002). Moreover, reward dependence, a putatively heritable trait associated with maintenance of behavior in response to reward cues, shows trait-like features associated with familiality of depression (Farmer et al, 2003).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In line with this hypothesis, studies have found that anhedonia can precede the onset of depression (Dryman and Eaton, 1991); shows temporal stability (Oquendo et al, 2004); predicts poor outcome 12 months later (Spijker et al, 2001); and is associated with dysfunctions within the brain reward system (Keedwell et al, 2005;Tremblay et al, 2002). Moreover, reward dependence, a putatively heritable trait associated with maintenance of behavior in response to reward cues, shows trait-like features associated with familiality of depression (Farmer et al, 2003).…”
Section: Discussionmentioning
confidence: 88%
“…These dysfunctions may in turn foster the generation, maintenance, and/or exacerbation of depressive symptoms, particularly lack of interest in the environment and loss of pleasure. Studies using self-report measures have indeed shown that anhedonia and blunted behavioral activation predicted (1) future depressive symptoms (Hundt et al, 2007;Kimbrel et al, 2007), (2) course of depression and time to recovery (McFarland et al, 2006), and (3) poor treatment outcome 8-12 months later (Kasch et al, 2002;Spijker et al, 2001). Moreover, low positive affect has been identified as a risk factor for the development and maintenance of depressive symptoms in children (Hayden et al, 2006;Joiner and Lonigan, 2000;Lonigan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Educational level was also omitted because it potentially confounds with other variables that may be of influence on course. 20 Inclusion of all these variables would call for unacceptable complex analyses given the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to investigate the role of anhedonia in pain, because it specifically predicts worse treatment outcome [32] and a longer and more severe course of depression [33]. The purpose of the current study was to examine whether BDNFTrkB signaling might contribute to the individual differences in anhedonia-like phenotype in rats after spared nerve injury (SNI).…”
Section: Introductionmentioning
confidence: 99%